З історії протипожежної служби Миколаєва (1920-ті рр.) - Пархоменко, В. (Краєзнавство, 2018)
У статті висвітлено становлення та розвиток протипожежної служби м. Миколаєва у 1920-х роках. Основними джерелами дослідження стали матеріали державного архіву Миколаївської області та
періодичні видання тих років. В публікації простежено виконання миколаївськими пожежними, під керівництвом М. М. Свіжинського, своїх професійних обов'язків та покращення технічного забезпечення міської пожежної команди у перше десятиліття радянської влади. The article highlights the formation and development of the fire brigade in Mykolaiv in the 1920s. The main
sources of research were the materials of the State Archives of Mykolaiv region and periodicals of those years.
The process of reorganization of the city fire brigade at the beginning of 1920s is highlighted. In particular,
the difficulties with the restoration of its material and technical base in Mykolayiv and the suburbs during the postrevolutionary
period were shown.
The author emphasized the merits of captain M. N. Svizhynsky (led the city bregade since 1910) in reorganization
of Mykolaiv fire service, which was one of the best in the country in that period.
The participation of Mykolaiv firefighters in the elimination of resonant fires, in particular at the Mykolaiv
elevators in April 1923. The state of fire service at the Mykolaiv factories is shown: «Tremsud» («Shipbuilding
Trust»), named after Andre Marti and the commercial port.
Re-equipment of these enterprises from the second half of the 1920s with new specialized equipment is shown.
The conclusions analyze the fulfillment by the Mykolaiv firemen (under the leadership of M. N. Svizhinsky)
their professional duties and improving the technical support of the city fire brigade in the first decade of Soviet
power. В статье отражено становление и развитие противопожарной службы г. Николаева в 1920-х годах.
Основными источниками исследования стали материалы государственного архива Николаевской области и периодические издания тех лет. В публикации прослежено выполнение николаевскими пожарными,
под руководством М. Н. Свижинского, своих профессиональных обязанностей и улучшение технического
обеспечения городской пожарной команды в первое десятилетие советской власти.